Mean Variance Vulnerability - Eichner, Thomas (Management Science, 2008)
This paper transfers the concept of Gollier and Pratt's (Gollier, C., J. W. Pratt. 1996. Risk vulnerability and the tempering effect of background risk. Econometrica 64 1109–1123) risk vulnerability into mean variance preferences. Risk vulnerability is shown to be equivalent to the slope of the mean variance indifference curve being decreasing in mean and increasing in variance. Next, we introduce the notion of mean variance vulnerability to link the concepts of decreasing absolute risk aversion, risk vulnerability, properness, and standardness. All of the abovementioned concepts are characterized in terms of mean variance indifference curve properties and in terms of absolute risk measures.